A Comparative Analysis of Online and Offline Purchase Regarding After Sales Service of Smart Phones in Ahmedabad City - Soni, Rajvi; Patel, Bansi; Vidani, Jignesh (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
The rapidly changing nature of the retail environment, which is hence prompted by technological development and changes in the pattern of consumer behavior, brings tremendous transformations in smartphone buying and after-sales service. This study thus sets its target to undertake a comparative analysis of the after-sales service of purchasing smart phones online as well as offline in the city of Ahmedabad. With the burgeoning expansion of the e-commerce sector, ease of purchasing and wide varieties available online have increased an individual's preference for online shopping. However, there are doubts about the quality and efficiency of after-sales services. Offline retailing has also preserved its personal, immediate service while lagging in convenience and integration with technologies. Consumer perception, service quality, and accessibility in terms of satisfaction regarding online and offline contexts are analysed using a mixed-methods approach involving surveys and interviews. The findings have indicated paramount differences in consumer experiences across delivery services, hence an implied need for retailers and manufacturers to tailor their strategies accordingly to the changing needs of the customers. This research contributes deeper knowledge to the after-sales service dynamics and actionable recommendations for the improvement of customer satisfaction in both online and offline retail environments